2015
DOI: 10.1016/j.jweia.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Near-ground turbulence of the Bora wind in summertime

Abstract: Bora is a strong, temporally and spatially variable downslope wind that blows along the Eastern Adriatic Coast and many other dynamically similar places around the world. Bora mean velocity rarely exceeds 20 m/s, while its strong gusts create significant problems for engineering structures, traffic and agriculture. Previous meteorological and geophysical studies laid foundations on Bora large-and mesoscale motions, but further research is necessary to fully understand and resolve Bora turbulence in a form usab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Recently, microscale properties of Bora have been investigated for different Bora types [20], confirming most of previous results related to Bora periodicity and turbulence properties [21,22]. Bora turbulence properties were studied in [23,24] as well, with a particular focus on turbulence intensity, Reynolds shear stress, and turbulence length scales. Research at specific regions in Croatia (Pometeno brdo near Split [22] and Maslenica [20]), revealed that the near-ground wind speed profile of Bora is in good agreement with the logarithmic law and power law description, which are commonly used in wind engineering.…”
Section: Introductionsupporting
confidence: 71%
“…Recently, microscale properties of Bora have been investigated for different Bora types [20], confirming most of previous results related to Bora periodicity and turbulence properties [21,22]. Bora turbulence properties were studied in [23,24] as well, with a particular focus on turbulence intensity, Reynolds shear stress, and turbulence length scales. Research at specific regions in Croatia (Pometeno brdo near Split [22] and Maslenica [20]), revealed that the near-ground wind speed profile of Bora is in good agreement with the logarithmic law and power law description, which are commonly used in wind engineering.…”
Section: Introductionsupporting
confidence: 71%
“…The hill models were designed to closely represent realistic terrain conditions that commonly appear in the full-scale, e.g. Lepri et al [34], [35], rather than some generic shape. 16 TRANSACTIONS OF FAMENA XLIII-3 (2019) Each hill model is 600 mm long in the main flow direction (along the wind tunnel test section) and 1000 mm wide (lateral to the main flow direction).…”
Section: Methodsmentioning
confidence: 99%
“…They also found that thermal stratification of the surface layer is near neutral due to strong mechanical mixing. Using the same data, Lepri et al [1,36] further investigated turbulence intensity, Reynolds shear stress and turbulence length scale profiles for the mentioned location.…”
Section: Introductionmentioning
confidence: 99%